1996
DOI: 10.1126/science.273.5276.801
|View full text |Cite
|
Sign up to set email alerts
|

Central Hypotensive Effects of the α 2a -Adrenergic Receptor Subtype

Abstract: alpha2-Adrenergic receptors (alpha2ARs) present in the brainstem decrease blood pressure and are targets for clinically effective antihypertensive drugs. The existence of three alpha2AR subtypes, the lack of subtype-specific ligands, and the cross-reactivity of alpha2AR agonists with imidazoline receptors has precluded an understanding of the role of individual alpha2AR subtypes in the hypotensive response. Gene targeting was used to introduce a point mutation into the alpha2aAR subtype in the mouse genome. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
313
2
5

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 455 publications
(337 citation statements)
references
References 13 publications
17
313
2
5
Order By: Relevance
“…Our results support the data of Tolentino-Silva et al (2000) showing that moxonidine, another imidazoline-like drug, induces hypotension in D79N mice lacking functional a 2A ARs. This however does not corroborate the data of MacMillan et al (1996) obtained in the same strain of mice.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results support the data of Tolentino-Silva et al (2000) showing that moxonidine, another imidazoline-like drug, induces hypotension in D79N mice lacking functional a 2A ARs. This however does not corroborate the data of MacMillan et al (1996) obtained in the same strain of mice.…”
Section: Discussioncontrasting
confidence: 99%
“…The D79N mouse line was created using a hit and run gene targeting strategy (18), as described (8). Male chimeras were mated with C57BL͞6 mice to generate heterozygous mice for intercrosses.…”
Section: Methodsmentioning
confidence: 99%
“…We used the ''hit and run'' targeting variant of homologous recombination (6,7) to substitute a subtle mutation of the ␣ 2a AR, D79N into the mouse genome as a tool to explore the role of the ␣ 2a AR in vivo (8). The aspartate residue at position 79 (D79) is highly conserved in a topologically identical position in the second transmembrane span in a large subset of G protein-coupled receptors (9).…”
mentioning
confidence: 99%
“…Conversely, a vasopressor response may be elicited by the central action of an a 2 -adrenoceptor antagonist (Goldberg et al, 1983). In mice with a point mutation of a 2A -adrenoceptors, the sustained decrease in blood pressure was absent (MacMillan et al, 1996), suggesting that centrallyinduced hypotension is induced via stimulation of a 2A -adrenoceptors. Because of the very low a nity of OPC-28326 for a 2A -adrenoceptors, the central antagonistic actioninduced pressor response may be weak.…”
Section: Discussionmentioning
confidence: 99%
“…In mice lacking a 2B -adrenoceptors, the pressor response induced by an a 2 -adrenoceptor agonist was absent (Link et al, 1996). The central hypotensive action of the a 2 -adrenoceptor agonist was absent in mice lacking the a 2A -adrenoceptors (MacMillan et al, 1996). It has also been reported that presynaptic a 2 -adrenoceptors are similar to a 2A -adrenoceptors (Smith & Docherty, 1992;Daniel et al, 1995).…”
Section: Opc-28326mentioning
confidence: 98%